Ethanol production from Banana stem (Musa paradisiaca linn) using two-sequential steps of dilute sulfuric acid hydrolysis and yeast fermentation. - Valera, Jessebel Patchicoy (2009.)
Alternatives to petroleum-derived fuels are being sought in order to reduce world's dependence on non-renewable sources. the most common renewable fuel today is ethanol derived from cellulosic biomass, called bioethanol (Anderson, 2006). Production and use of ethanol for fuel can reduce air pollution, increase employment and reduce global change-carbon dioxide buildup (w.w.w. estru.strath.ac.uk). In this study, different concentrations of sulfuric acid were compared ( 5 percent H2SO4, 10 percent H2SO4 and 20 percent H2SO4) which among them has the highest glucose yield. And among them 5 percent H2SO4 hydrolyzed most of the sample into simpler sugar units. using two-sequential steps of acid hydrolysis and yeast (Saccharomyces cerevisae; glucose-fermenting yeast) fermentation, bioconversion of banana stem, Musa paradisiacal Linn, to liquid ethanol has been performed. During yeast fermentation of pH 5.6 and room temperature, the maximum glucose yield of 70.18 mg/kg banana stem and ethanol yield of 2.69 percent was achieved. The glucose content of the hydrolysate was performed using UV-VIS spectrometry. Anthrone assay (Mokrasch, 1953 and Rhodes, 1996). Furthermore , the fermented ethanol was subjected to simple distillation for isolation and purification purpose and the ethanol obtained was then assayed using refractometer
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Banana Stem; Musa paradisiaca linn